2019
DOI: 10.1186/s12885-019-6197-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative research on 99mTc-Rituximab and 99mTc-sulfur colloid in sentinel lymph node imaging of breast cancer

Abstract: Background 99mTc-Rituximab is a new specific radiopharmaceutical that binds to the CD20 receptor which is highly expressed on the surface of B cells. We conducted a study in which 99mTc-Rituximab was compared with filtered 99mTc-sulfur colloid (fTcSC) for sentinel lymph node (SLN) detection in patients with breast cancer. Method The study is divided into three parts. 1. Initially, 25 patients were selected for an internal controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
(18 reference statements)
0
4
0
4
Order By: Relevance
“…In 2015, a multi‐center prospective study coordinated by the International Atomic Energy Agency published the added value of SPECT/CT on planar scintigraphy in various malignant tumors, including primary breast cancer, and it showed that the visualization rate of SLN increased from 87.6% to 91.3% after adding SPECT/CT 9 . The SLN recognition rates of 99m Tc‐Rituximab and 99m Tc‐sulfur colloid guided SPECT/CT in the axillary area were 100% and 98.4%, respectively, and 98.5% and 98.7 in all areas 10 . Compared with lymphangiography alone, SPECT/CT has obvious advantages in the detection of internal breast LNs 11 and ipsilateral axillary external drainage 12,13 .…”
Section: Isotopic Tracer Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2015, a multi‐center prospective study coordinated by the International Atomic Energy Agency published the added value of SPECT/CT on planar scintigraphy in various malignant tumors, including primary breast cancer, and it showed that the visualization rate of SLN increased from 87.6% to 91.3% after adding SPECT/CT 9 . The SLN recognition rates of 99m Tc‐Rituximab and 99m Tc‐sulfur colloid guided SPECT/CT in the axillary area were 100% and 98.4%, respectively, and 98.5% and 98.7 in all areas 10 . Compared with lymphangiography alone, SPECT/CT has obvious advantages in the detection of internal breast LNs 11 and ipsilateral axillary external drainage 12,13 .…”
Section: Isotopic Tracer Methodsmentioning
confidence: 99%
“… 9 The SLN recognition rates of 99m Tc‐Rituximab and 99m Tc‐sulfur colloid guided SPECT/CT in the axillary area were 100% and 98.4%, respectively, and 98.5% and 98.7 in all areas. 10 Compared with lymphangiography alone, SPECT/CT has obvious advantages in the detection of internal breast LNs 11 and ipsilateral axillary external drainage. 12 , 13 It is also useful for scanning invisible, unexplained, or unexpected SLNs (Figure 1 ).…”
Section: Isotopic Tracer Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Одним из таких РФЛП на данный момент является [ 99m Tc]-ритуксимаб, который связывается с рецептором CD20 активно экспрессирующихся на поверхности В-клеток. Проведенные исследования показали, что [ 99m Tc]-ритуксимаб в меньшей степени перераспределяется в дистальные лимфоузлы, по сравнению с коллоидными РФЛП, и активнее уходит из места инъекции [16]. Также на сегодняшний день в США зарегистрирован и актив-но внедряется в клинику Lymphoseek™, меченный 99m Tc, который накапливается в лимфатических узлах путем связывания с CD206 на поверхности макрофагов [17].…”
Section: __________________________unclassified
“…The first case is the 99mTc-colloid (99mTc-Nanocoll ® ) a nano-colloid albumin deserve attention. This radioactive nanodrug has been approved for lymph nodes imaging in EU (Gommans et al., 2001 ; Mariani et al., 2001 ; Gommans et al., 2009 ) and a modified version of the original 99mTc-Nanocoll using sulfur in the colloidal state (99mTc-Technecoll ® ) has been approved in USA for nodal detection in melanoma, prostate and breast cancer (Alazraki et al., 1997 ; Holl et al., 2009 ; Seok et al., 2010 ; Ganswindt et al., 2011 ; Seo et al., 2011 ; Zhang et al., 2019 ). Back in the 80-90’s was developed and clinically evaluated an 111In-encapsulating liposome formulation (Vescan) for detection of carcinoma and metastases of prostate, lung and breast cancer (Presant et al., 1994 ; Jensen and Bunch, 2007 ).…”
Section: Clinical Application and Trialmentioning
confidence: 99%